2005
DOI: 10.1002/jae.835
|View full text |Cite
|
Sign up to set email alerts
|

Inefficiency and heterogeneity in Turkish banking: 1990–2000

Abstract: SUMMARYRecent studies have stressed the importance of privatization and openness to foreign competition for bank efficiency and economic growth. We study bank efficiency in Turkey, an emerging economy with great heterogeneity in bank types and ownership structures. Earlier studies of Turkish banking had three limitations: (i) excessive reliance on cost-function frontier analyses, wherein volume of loans is a measure of banking output; (ii) pooling all banks or imposing ad hoc heterogeneity assumptions; and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 43 publications
(40 reference statements)
2
45
0
Order By: Relevance
“…The evidence from previous empirical studies of Islamic and conventional banking is mixed: some find no significant difference in efficiency between the two types of banking (Abdul-Majid et al 2005b;El-Gamal and Inanoglu 2005;Mokhtar et al 2006;Bader 2008;Hassan et al 2009;Shahid et al 2010); some studies do not test whether observed differences in efficiency are significant and this is mainly due to small sample size (Hussein 2004;Al-Jarrah and Molyneux 2005;Said 2012). One study (Al-Muharrami 2008) claims that Islamic banks are significantly more efficient 8 An alternative approach using data mining can be found elsewhere (Emrouznejad and Anouze 2009;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evidence from previous empirical studies of Islamic and conventional banking is mixed: some find no significant difference in efficiency between the two types of banking (Abdul-Majid et al 2005b;El-Gamal and Inanoglu 2005;Mokhtar et al 2006;Bader 2008;Hassan et al 2009;Shahid et al 2010); some studies do not test whether observed differences in efficiency are significant and this is mainly due to small sample size (Hussein 2004;Al-Jarrah and Molyneux 2005;Said 2012). One study (Al-Muharrami 2008) claims that Islamic banks are significantly more efficient 8 An alternative approach using data mining can be found elsewhere (Emrouznejad and Anouze 2009;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first error component, Given these distributional assumptions, the log-likelihood function is [4,5], 14 Each of the j technologies share the same distributional parameters for without this assumption [8].…”
Section: Estimationmentioning
confidence: 99%
“…They estimate the following heterogeneous production function, To estimate the heterogeneous production function the El-Gamal and Grether estimation classification (EC) algorithm is used Grether 1995, 2000). In addition to Schnier et al's use of the EC algorithm, this method has recently been used by El-Gamal and Inanoglu (2005) to 3 Average vessel speed was provided by contacts at Woods Hole Oceanographic Institute. For a more detailed description of the data utilized and the methodology used to obtain the hours fished see Schnier et al (2006).…”
Section: Methodsmentioning
confidence: 99%